Microbial growth on C1 compounds - Murrell, J. C. (J. Colin); Kelly, Don P.; International symposium on Microbial Growth on C1 Compounds (7th : 1992 : University of Warwick) (Andover, UK : Intercept Ltd., 1993)
42